A European career guidance concept for international youth mobility - Kreutzer, Florian [Verfasser]; Iuga, Elena [Verfasser] (Bertelsmann, 2016)
"The goal of international career guidance is to help young people to make a proper career choice and to support them as they progress in their planning of moving abroad. This practice-oriented eGuidance Concept focuses on a systematic elaboration of European career guidance methods based on the target's group needs. It has been realized by the active involvement of the target group of EURES and other counsellors. The aim fo the eGuidance Concept lies within merging it with new technologies and digital learning equipment as a chance to a new and further development of an efficient, low-threshold, low cost and open access eLearning and teaching opportunity for EURES and other counsellors." (Publisher, BIBB-Doku)

"Wie berät man Jugendliche und junge Menschen optimal, die eine Ausbildung, ein Studium oder einen Beruf im Ausland beginnen möchten? Der Band stellt das eGuidance-Konzept für Berufs- und Ausbildungsberater vor, das im Rahmen eines europäischen Projektes entwickelt und erprobt wurde. Es ist eine Weiterbildung mit dem Schwerpunkt berufliche Jugendmobilität für nationale, regionale und lokale Ausbildungsberater in ganz Europa. Kern ist eine neue Form der virtuellen Beratung, um überall erreichbar zu sein. Online-Materialien und -Tools stehen auf den Projektwebsites www.guidemyway.eu oder www.guide-my-way.eu zur Verfügung und ergänzen das Informationsangebot des Bandes." (Verlag)
Keywords: L 5.3 Bildungs(gang)beratung; G 1.3.3.3 Mobilität; P 1.1 Jugendliche; I 2.2 Europa; Bildungsberatung; Jugendlicher; Berufliche Mobilität; Europa